Biomarker responses of cardiac oxidative stress to high intensity interval training in rats - Lúcio Marques Vieira-Souza; Jymmys Lopes dos Santos; Anderson Carlos Marçal; Fabrício Azevedo Voltarelli; Felipe José Aidar; Rodrigo Miguel-; Roas de Araújo Costa; Dihogo Gama de Matos; Sandra Lauton Santos; Silvan Silva de Araújo (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The present study aimed to verify the cardiac oxidative stress biomarker responses to high-intensity interval training (HIIT) in rats. Methods: Sixteen male Wistar rats weighing 250 to 300 g were equally divided into two groups (8 animals/group): sedentary control (SC) and trained group (HIIT). The exercise protocol consisted of high-intensity swimming (14% of body weight, 20 s of activity with 10 s of pause performed 14 times) which was performed for 12 consecutive days. Results: The cardiac tissue concentrations of malondialdehyde and carbonylated proteins showed no significant changes; on the other hand, hydroperoxide levels were higher in the HIIT group than in the SC group. The activities of superoxide dismutase, catalase, and glutathione peroxidase enzymes and the levels of reduced glutathione and sulfhydryl remained unchanged. Conclusion: It is possible to conclude that short-term high-intensity interval training induces changes in the cardiac oxidative stress biomarker but with no effect on the antioxidant enzymes.